2021
DOI: 10.1002/ece3.7543
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene climate fluctuations as the major driver of genetic diversity and distribution patterns of the Caspian green lizard, Lacerta strigata Eichwald, 1831

Abstract: Green lizards of the genus Lacerta have served as excellent models for studying the impact of Pleistocene climatic oscillations on genetic structures. The Caspian green lizard, Lacerta strigata , occupies various habitats across the Caucasus and the South Caspian Sea, with the Hyrcanian Forests and north of the Alborz Mountains forming the core of the range. This study aimed to re‐examine the phylogenetic relationships of L. strigata with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…It seems that the presence of two groups of R. pseudodalmatina in the west and east of the distribution may indicate the long-term residence within two different glacial refugia during the Pleistocene. The existence of cryptic refugia and the idea of "refugia-within-refugia" in the Hyrcanian forests that is proposed here for R. pseudodalmatina has been previously discussed for other species that live in this region (Ahmadi et al, 2018;Ahmadzadeh, Flecks, et al, 2013;Saberi-Pirooz et al, 2021). The assessments of demographic history revealed that the recent expansion occurred in the populations (Table 1 and Figure 3).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It seems that the presence of two groups of R. pseudodalmatina in the west and east of the distribution may indicate the long-term residence within two different glacial refugia during the Pleistocene. The existence of cryptic refugia and the idea of "refugia-within-refugia" in the Hyrcanian forests that is proposed here for R. pseudodalmatina has been previously discussed for other species that live in this region (Ahmadi et al, 2018;Ahmadzadeh, Flecks, et al, 2013;Saberi-Pirooz et al, 2021). The assessments of demographic history revealed that the recent expansion occurred in the populations (Table 1 and Figure 3).…”
Section: Discussionmentioning
confidence: 56%
“…The species composition and diversity of the Southwest Asian forests, rich in endemic species, suggests that the Hyrcanian region has likely acted as a glacial refugium for many taxa during the Quaternary glaciations (Röhrig, 1991;Saberi-Pirooz et al, 2018). Phylogeographic studies and climatic models have shown that the southern Caspian Sea has acted as a glacial refugium for a broad range of taxa, including Iranian rock lizards (Darevskia chlorogaster and Darevskia defilippii, Ahmadzadeh, Flecks, et al, 2013), Iranian brown bears (Ursus arctos, Ashrafzadeh et al, 2016), fat dormouse (Glis glis, Ahmadi et al, 2018), Persian mountain salamanders (Paradactylodon persicus, Ahmadzadeh et al, 2020), and Caspian green lizard (Lacerta strigata, Saberi-Pirooz et al, 2021). During the last halfcentury, the climate became warmer in the Hyrcanian forests, with the average annual temperature increasing between 1.28 and 2.45℃ and annual precipitation declining between 55.6 and 409.4 mm (Tohidifar et al, 2016).…”
mentioning
confidence: 99%
“…A similar effect has been outlined for evolution of several other aquatic species in the south Caspian basin (e.g., Sands et al, 2019 ), including the radiation of Ponticola hircaniaensis (Zarei, Esmaeili, Kovačić, et al, 2022a ) and a possible bottleneck in Proterorhinus nasalis (Zarei, Esmaeili, Schliewen, & Abbasi, 2022b ). Evolution in south Caspian refugia have been also reported for several species in other groups, e.g., rock lizards of the genus Darevskia , Arribas, 1999 (Ahmadzadeh et al, 2013 ; Saberi‐Pirooz et al, 2018 ), the Caspian green lizard Lacerta strigata Eichwald, 1831 (Saberi‐Pirooz et al, 2021 ), the Caucasian pit viper Gloydius halys caucasicus (Nikolsky, 1916) (Asadi et al, 2019 ), the Anatolian mountain frogs of the genus Rana Linnaeus, 1758 (Veith et al, 2003 ), and the freshwater crab Potamon ibericum (de Bieberstein, 1808) (Parvizi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 71%
“…Evolution in south Caspian refugia have been also reported for several species in other groups, e.g., rock lizards of the genus Darevskia, Arribas, 1999 (Ahmadzadeh et al, 2013;Saberi-Pirooz et al, 2018), the Caspian green lizard Lacerta strigata Eichwald, 1831 (Saberi-Pirooz et al, 2021), the Caucasian pit viper Gloydius halys caucasicus (Nikolsky, 1916) (Asadi et al, 2019), the Anatolian mountain frogs of the genus Rana Linnaeus, 1758 (Veith et al, 2003), and the freshwater crab Potamon ibericum (de Bieberstein, 1808) (Parvizi et al, 2018).…”
Section: Evolutionary History and Genetic Structurementioning
confidence: 66%
“…Phenotypic variation is the raw material for natural selection through which fitness is optimized via effects on survival and reproduction (van Buskirk et al, 1997). Climate is an important factor affecting the biogeographical distribution and species evolution (Li et al, 2016;Saberi-Pirooz et al, 2021). The phenotypic variation in vertebrates is generally associated with climatic factors, especially in ectotherms, through such factors as the effects of temperature and precipitation on body size (Wen and Fu, 2020), body shape (Gvodk et al, 2010), and head traits (Rainha et al, 2021) in amphibians and scale number (Wegener et al, 2014) and head traits (Jaffe et al, 2016) in reptiles.…”
Section: Introductionmentioning
confidence: 99%